Speculative art histories : analysis at the limits - Tuinen, Sjoerd van, 1978- (Edinburgh : Edinburgh University Press, 2017)
First full-scale thematic analysis of Pina Bausch's Tanztheater, critically evaluating the impact of modernist theatre on her choreographic method.
Machine generated contents note: 1. Asynchronous Present Past / Armen Avanessian -- 2. (Dis)Enchanted Taiwanese Cinema, Schizoanalytic Belief And The Actuality Of Animism / Erik Bordeleau -- 3. Attractors And Locked-In Art: Art History As A Complex System / Francis Halsall -- 4. Enduring Habits and Artwares / Adi Efal -- 5. Mood (Stimmung) / Blandness (Fadeur): On Temporality and Affectivity / Vlad Ionescu -- 6. The Plasticity of the Real: Speculative Architecture / Elisabeth von Samsonow -- 7. Expressive Things: Art Theories of Henri Focillon and Meyer Schapiro Reconsidered / Kerstin Thomas -- 8. Gothic Ontology and Sympathy: Moving Away From the Fold / Lars Spuybroek -- 9. Serpentine Life: The Nature of Movement In Gothic, Mannerism and Baroque / Sjoerd van Tuinen -- 10. Space Always Comes After: It Is Good When It Comes After; It Is Good Only When It Comes After / Andrej Radman -- 11. Speculation, Critique, Constructivism: Notions for Art History / Kamini Vellodi -- 12. The Potentiality of Art, the Force of Images and Aesthetic Intensities / Bertrand Prevost -- 13. Impossible! Bergson After Duchamp After Caillois / Sarah Kolb -- 14. Economies of the Wild: Speculations On Constant's New Babylon and Contemporary Capitalism / Bram Ieven -- 15. From Etienne Souriau's the Shadow of God to Mats Ek's Shadow of Carmen / Fleur Courtois-l'Heureux.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Art -- Philosophy -- Congresses; Art -- Philosophie -- Congrès.; ART -- General; Art -- Philosophy; k -- Conference -- v -- Papers (document genres); Conference papers and proceedings